Understanding key mechanisms of successfully leading integrated team-based services in health and social care: protocol for a realist synthesis. Issue 7 (9th July 2020) - Harris, Ruth; Fletcher, Simon; Sims, Sarah; Ross, Fiona; Brearley, Sally; Manthorpe, Jill
Abstract : Introduction: As systems of health and social care in England move towards more integrated and collaborative models, leaders will need different skills than their predecessors to enable system leadership, building partnerships and working across organisations and sectors. There is little understanding of what the mechanisms for effective leadership across integrated health and social care systems might be, the contexts that influence good leadership, or the nature of the resulting outcomes. This review aims to identify, refine and test programme theories of leadership of integrated team-based services in health and social care, exploring what works, for whom and in what circumstances. Methods and analysis: This study uses a realist synthesis approach, following RAMESES guidelines, supported by stakeholder consultation. Stage 1 will develop initial programme theories about leadership of integrated health and social care based on a review of the scientific and grey literature and a stakeholder consultation workshop. Stage 2 will involve focused searching of empirical literature, data extraction and synthesis to refine the initial programme theories and identify relationships between identified contexts, mechanisms and outcomes. A second stakeholder event will guide the focus of the review. Stage 3 will further refine and interrogate the theories testing them against substantive theory on leadership of complex systems and through the experiences and expertise of the stakeholder group. Ethics and dissemination: Our study does not require ethics committee approval. This research will contribute to building an in-depth understanding of what aspects of leadership of integrated team-based services work, for whom and in what circumstances. It will identify the professional development needs of leaders and provide recommendations about optimal organisational and interorganisational structures and processes that support effective leadership in integrated health and social care systems. Findings will be disseminated through peer-reviewed journal publications, conference presentations and formal and informal reports. PROSPERO registration number: CRD42018119291